2014
DOI: 10.1186/1475-2891-13-63
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxybenzoic acid isomers and the cardiovascular system

Abstract: Today we are beginning to understand how phytochemicals can influence metabolism, cellular signaling and gene expression. The hydroxybenzoic acids are related to salicylic acid and salicin, the first compounds isolated that have a pharmacological activity. In this review we examine how a number of hydroxyphenolics have the potential to ameliorate cardiovascular problems related to aging such as hypertension, atherosclerosis and dyslipidemia. The compounds focused upon include 2,3-dihydroxybenzoic acid (Pyrocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 88 publications
4
80
0
1
Order By: Relevance
“…Its quantity as determined by HPLC was 1.772 ± 0.022 mg/g DS (Table ), which was much higher than the reported value in Khalas date seeds (0.079 mg/g; Habib and others ). Generally, protocatechuic acid is not considered a major contributor in human dietary polyphenol intake due to its low contents in edible plants (0.27 mg/g fresh weight in blackberry and 0.1 mg/g fresh weight in raspberry) (D'Archivio and others ; Juurlink and others ). However, the high level of protocatechuic acid detected in Deglet Nour date seed FPP suggests the possible utilization of DSP as a better source of protocatechuic acid for nutraceutical use.…”
Section: Resultsmentioning
confidence: 99%
“…Its quantity as determined by HPLC was 1.772 ± 0.022 mg/g DS (Table ), which was much higher than the reported value in Khalas date seeds (0.079 mg/g; Habib and others ). Generally, protocatechuic acid is not considered a major contributor in human dietary polyphenol intake due to its low contents in edible plants (0.27 mg/g fresh weight in blackberry and 0.1 mg/g fresh weight in raspberry) (D'Archivio and others ; Juurlink and others ). However, the high level of protocatechuic acid detected in Deglet Nour date seed FPP suggests the possible utilization of DSP as a better source of protocatechuic acid for nutraceutical use.…”
Section: Resultsmentioning
confidence: 99%
“…A new class of fibroblast growth factor inhibitors potentially relevant to the treatment of cancer and angiogenesis‐related diseases has been defined based on gentisic acid . In addition, hydroxybenzoic acids have been reported to attenuate factors associated with cardiovascular diseases, such as hypertension, atherosclerosis and dyslipidaemia . Recently, we demonstrated that gentisic acid is the third most abundant polyphenol compound in Dendropanax morbifera branch extracts and reduces isoproterenol‐induced cardiomyocyte hypertrophy (paper under review).…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid (20) Z. clinopodioides [80] Effect on cardiovascular system reviewed [117] Pharmacological importance reviewed [118] Molecules 2016, 21, 826 7 of 53…”
Section: O Omentioning
confidence: 99%
“…clinopodioides [44,80] Inhibition of mucin production and secretion in airways epithelial cells [83] Hepatoprotective [84] Potential inhibitor of CDK4 in retinoblastoma [85] Neuroprotective [86] Inhibition of acetylcholinesterase [87] Anti-inflammatory [88]; Anti-inflammatory in vivo [89] Depressant effect on CNS [ [80] Effect on cardiovascular system reviewed [117] Pharmacological importance reviewed [118] O H…”
Section: Linarin (8)mentioning
confidence: 99%
See 1 more Smart Citation